Effects of dietary supplements on selected hematological and biochemical parameters of Pakistani athletes - Jahan, Sarwat (BMC Nutr, 2018)
BACKGROUND: CDC’s (Centers for Disease Control and Prevention) National Center for Health statistics recent reports have shown that an upsurge has occurred in the use of dietary supplements among age of 20 years since 1994 and this use shown regular increase. The purpose of our study was to investigate the effect of supplements on the reproductive health on male athletes in Pakistan. METHODS: A total of 150 adult male with mean age of 25.78 ± 0.56 years were included in this study and divided into four groups: Non-athlete control (n = 57), Non supplemental athlete control (n = 40), Supplemental athlete group I (n = 28) and supplemental athlete group II (n = 25). Blood (10 ml) was taken from each subject. Complete blood count was performed and 5 ml of blood was centrifuged to separate plasma and then analyzed for antioxidant enzyme (CAT, POD, GR and GSH) activities, Lipid peroxidation (TBARS), electrolyte, metal (sodium, potassium and zinc) and Luteinizing hormone (LH) concentration. RESULTS: Complete blood count results showed normal RBC, WBC, Platelets, Hemoglobin, Hematocrit, Mean corpuscular hemoglobin and Mean corpuscular hemoglobin concentration. Antioxidant enzymes (CAT, POD, GR, GSH) increased significantly in supplemental athletes as compared to control groups. Sodium and potassium showed significant increase (p < 0.001) in supplemental athlete group I, while TBARS also showed significant increase (p < 0.05) in supplemental group I and II as compared to non athlete control while non supplemental athletes showed significant increase (p < 0.05) in TBARS concentration as compared to non athlete control. LH concentration was found to be decreased significantly (p < 0.05) in supplemental group I and II as compared to control groups. CONCLUSION: It is therefore concluded from the present results that oxidative stress was considerably elevated in response to supplement consumption among athletes which may affect their health haematological parameters and reproductive hormones.